Trusting our trainees: competency-based training of cardiologists using Entrustable Professional Activities (EPA). (25th November 2020) - Beeri, R; Tanner, F.C; Ten Cate, O; Ros, M; Kirchhof, P
Abstract:  : Assessment of trainees is a core activity of educators, ensuring that trainees can be trusted to provide high quality care with no supervision. Training and the demands on trainees have changed with specialization, need for more technical skills, digitization, needs for teamwork and greater communication skills. Competency-based medical education was introduced to capture these changing needs for trainees. The 7th ESC Education Conference – "From competence to good clinical care" – brought together national directors of training (39), young cardiology representatives (7), patients (7), ESC partners in education (10), and the ESC Education Committee (22) to discuss contemporary challenges in cardiology training and Entrustable Professional Activities (EPAs)-based solutions. Methods: Pre- and post-conference surveys were conducted. The different issues were discussed in 4 workshops: core knowledge and evidence, skills and competence, performing into context, and training the trainers. Results: Pre-conference, 90% of respondents believed that trainees should be certified only when they can be entrusted to perform in an unsupervised fashion, and 84% thought that specific training for educators should be required. From the workshops 4 themes emerged: 1) Core knowledge and evidence: rotations to different centres are needed to enable trainees to meet EPA requirements. 2) Skills and competence: a learning agreement between trainers and trainees should be established with protected time to achieve EPAs, and patient feedback on trainee performance should be obtained. 3) Performing into context (when is a trainee ready to practice): clinicians do informal assessment on a daily basis; EPAs formalize this with regular observation linked with progression in responsibility. 4) Train the trainer: good doctors are not automatically good trainers and should be required to undergo specific training themselves. We reviewed complex training frameworks such as the Canadian Medical Education Directives for Specialists (CanMEDS) that contains too many components to be useful for clinical teachers. EPAs were identified as a practical way to implement competency-based cardiology training across the ESC. The 2020 ESC Core Curriculum contains EPAs that a cardiologist should be able to perform independently by the end of training. Post-conference there was unanimous agreement (100%) that EPAs are a valuable concept in training. A majority of participants (69%) agreed that EPA's are applicable in practice today. Conclusion: Trainee assessment is a daily challenge for educators. The ESC Education Conference identified distinct goals to be achieved before, during and at the completion of a training programs. The EPA concept was widely accepted as an efficient method to monitor trainees progress, while trusting them to perform activities in which they are proficient. Trusting our trainees should be a major educational goals for cardiologists in Europe. Funding Acknowledgement: Type of funding source: None